Dietary intake patterns among lactating and non-lactating women of reproductive age in rural Zambia - Kaliwile, Chisela; Michelo, Charles; Titcomb, Tyler; Moursi, Mourad; Angel, Moira Donahue; Reinberg, Chelsea; Bwembya, Pheobe; Alders, Robyn; Tanumihardjo, Sherry A. (MDPI, 2019)
Insufficient dietary intake, micronutrient deficiencies, and infection may result in malnutrition. In Zambia, an estimated 14% of women are vitamin A-deficient, ~50% are anemic, 10% are underweight, and 23% are overweight/obese. A cross-sectional survey determined food and nutrient intakes of randomly selected Zambian women (n = 530) of reproductive age (15–49 years). Dietary intake data were collected using interactive multiple-pass 24-h recalls. Carbohydrate, fat, protein, and selected micronutrient intakes were estimated. Prevalence of adequate intakes were determined using the estimated average requirement (EAR) cut-point method and comparisons between lactating and non-lactating women were made by two-sample t-tests. The response rate was 98.7%. Overweight/obesity occurred in 20.7% (95% confidence interval (CI: 17.2, 24.5)). Almost all micronutrient intakes were inadequate, with values between 22.3% and 99.9%. Mean iron intake was >EAR, and 8.2% of women tested (12/146, 95% CI: 4.1, 13.0) were anemic (hemoglobin <115 g/L). Calcium intake was higher in lactating than non-lactating women (p = 0.004), but all intakes need improvement. Vitamin intakes in rural Zambian women are inadequate, suggesting a need for health promotion messages to encourage intake of locally available micronutrient-dense foods as well as supplementation, fortification, and biofortification initiatives. Nutritional support is important because maternal nutrition directly impacts child health.